Pengembangan Model Komunikasi Berbasis Network Society dan Mobile Content Management Dalam Model Pembelajaran dan Implikasinya Pada Gen Z Development Index di Jawa Barat - Ahmad, Gofur; Annas, Mohammad (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
This research aims to determine the correlation and influence of social networking, gadget content management on the development of quality generation Z in the three regions of the southern part of West Java Province, namely Bogor Regency, Banjar City and Cianjur Regency. Mixed qualitative and quantitative methods are carried out to obtain an initial overview of the conventional model learning process that has been applied, including exploring the readiness of technology and research object infrastructure, pre-test, post-test and the use of rubrics into control and free samples. Quantitative methods with the number of data samples processed as many as 306 performed to get the data then processed with SmartPLS software. The results showed that the use of information technology as a means of supporting learning is still very limited by the mindset that the device is considered more as a distractive factor and not a supporting factor for the learning process. The interactive learning and collaborative learning models are minimal, even though this method is considered most suitable for students with an equivalent level of secondary/ Tsanawiyah which are called generation Z.Â Keywords: komunikasi jejaring sosial, manajemen konten, index generasi Z